AKIGUARD (Acute Kidney Injury GUARding Device) trial: in-hospital and one-year outcomes. Issue 7 (July 2016) - Usmiani, Tullio; Andreis, Alessandro; Budano, Carlo; Sbarra, Pierluigi; Andriani, Monica; Garrone, Paolo; Fanelli, Anna Laura; Calcagnile, Chiara; Bergamasco, Laura; Biancone, Luigi; Marra, Sebastiano
Abstract : Aims: Contrast-induced acute kidney injury (CIAKI) in patients with chronic kidney disease undergoing coronary angiography or percutaneous coronary intervention is a common iatrogenic complication associated with increased morbidity and mortality. This study compares sodium bicarbonate/isotonic saline/ N -acetylcysteine/vitamin C prophylaxis (BS-NAC) against high-volume forced diuresis with matched hydration in CIAKI prevention. Methods: One-hundred and thirty-three consecutive patients undergoing coronary angiography or percutaneous coronary intervention with estimated glomerular filtration rate less than 60 mL/min/1.73m 2 were randomized to the study group receiving matched hydration (MHG) or to the control group receiving BS-NAC. MHG received in vein (i.v.) 250 mL isotonic saline bolus, followed by a 0.5 mg/kg furosemide i.v. bolus to forced diuresis. A dedicated device automatically matched the isotonic saline i.v. infusion rate to the urinary output for 1 h before, during and 4 h after the procedure. Results: MHG had the lowest incidence of CIAKI (7 vs. 25%, P = 0.01), major adverse cardiac and cerebrovascular events at 1 year (7 vs. 32%, P < 0.01) and readmissions to cardiology/nephrology departments (8 vs. 25%, P = 0.03; hospitalization days 1.0 ± 3.8 vs. 4.9 ± 12.5, P = 0.01). Three months after the procedure the decrease in the estimated glomerular filtration rate was 0.02% for MHG versus 15% for the control group. Conclusion: Matched hydration was more effective than BS-NAC in CIAKI prevention. One-year follow-up showed that matched hydration was associated also with limited chronic kidney disease progression, major adverse cardiac and cerebrovascular events and hospitalizations.